2019
DOI: 10.1002/ejoc.201900510
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐Assisted Domino Heck Cyclization and Phosphorylation: Synthesis of Phosphorus Containing Heterocycles

Abstract: A domino [Pd]‐catalyzed intramolecular Heck cyclization followed by intermolecular phosphorylation, for the construction of phosphorus containing heterocyclic compounds, is presented. Notably, the process is accelerated by microwave heating conditions and enabled the construction of C–C and C–P bonds in short reaction times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…In 2019, the same group developed Pd‐catalyzed intra‐ and intermolecular Heck cyclization followed by phosphorylation, respectively, to construct phosphorus‐containing heterocyclic compounds (dihydrobenzofurans) [96] . The formation of C−C and C−P bonds are facilitated in microwave irradiation in quick reaction times.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, the same group developed Pd‐catalyzed intra‐ and intermolecular Heck cyclization followed by phosphorylation, respectively, to construct phosphorus‐containing heterocyclic compounds (dihydrobenzofurans) [96] . The formation of C−C and C−P bonds are facilitated in microwave irradiation in quick reaction times.…”
Section: Resultsmentioning
confidence: 99%
“…According to the plausible mechanism, the Pd In 2019, the same group developed Pd-catalyzed intra-and intermolecular Heck cyclization followed by phosphorylation, respectively, to construct phosphorus-containing heterocyclic compounds (dihydrobenzofurans). [96] The formation of CÀ C and CÀ P bonds are facilitated in microwave irradiation in quick reaction times. In this protocol, the o-iodophenyl allyl ethers 35 were treated with diphenylphosphine oxide 46 to yield the phosphorylated dihydrobenzofurans 47, as illustrated in Scheme 5.…”
Section: Synthesis Of Dihydrobenzofurans By Using Microwave Irradiationmentioning
confidence: 99%
“…In 2019, Karu Ramesh [49] et al have reported the synthesis of phosphorous-containing heterocycles via microwave-assisted domino Pd-catalyzed intramolecular Heck cyclization followed by phosphorylation reaction (Scheme 18). The process intensified the formation of CÀ C and CÀ P bonds in short reaction times.…”
Section: Synthesis Of Indole/oxindole-based Heterocyclesmentioning
confidence: 99%
“…In the same year, Satyanarayana and Ramesh reported a palladium-catalyzed aerobic oxidative coupling of ortho -(alkynyl)styrenes and allylic alcohols via a 6- endo -dig annulation to obtain polysubstituted naphthalenes (Scheme 23 ). 48 The optimum conditions for this intramolecular cycloaromatization involved the use of PdCl 2 in an open-air atmosphere. The plausible catalytic cycle begins with coordination of the Pd(II) species to the triple bond of the styrene substrate, with the resulting intermediate undergoing an intramolecular 6- endo -dig cyclization via formation of a carbocation intermediate and HX elimination to restore the aromaticity.…”
Section: Oxidative C–c and C–nu Couplingmentioning
confidence: 99%